A semi‐Markov model comparing the lifetime cost‐effectiveness of mesh prophylaxis to prevent parastomal hernia in patients undergoing end colostomy creation for rectal cancer. (12th August 2021) - Mohiuddin, Syed; Reeves, Barnaby C.; Smart, Neil J.; Hollingworth, William; ,
Abstract: Aim: Parastomal hernia (PSH) is a common problem following colostomy. Using prophylactic mesh during end colostomy creation may reduce PSH incidence, but concerns exist regarding the optimal type of mesh, potential long‐term complications, and cost‐effectiveness of its use. We evaluated the cost‐effectiveness of mesh prophylaxis to prevent PSH in patients undergoing end colostomy creation for rectal cancer. Methods: We developed a decision‐analytical model, stratified by rectal cancer stages I–IV, to estimate the lifetime costs, quality‐adjusted life‐years (QALYs) and net monetary benefits (NMBs) of synthetic, biologic and no mesh from a UK NHS perspective. We pooled the mesh‐related relative risks of PSH from 13 randomised controlled trials (RCTs) and superimposed these on the baseline (no mesh) risk from a population‐based cohort. Uncertainty was assessed in sensitivity analyses. Results: Synthetic mesh was less costly and more effective than biologic and no mesh to prevent PSH for all rectal cancer stages. At the willingness‐to‐pay threshold of £20, 000/QALY, the incremental NMBs (95% CI) ranged between £1, 706 (£1, 692 to £1, 720) (stage I) and £684 (£678 to £690) (stage IV) for synthetic versus no mesh, and £2, 038 (£1, 997 to £2, 079) (stage I) and £1, 671 (£1, 653 to £1, 689) (stage IV) for synthetic versus biologic mesh. Synthetic mesh was more cost‐effective than no mesh unless the relative risk of PSH was ≥0.95 for stages I–III and ≥0.93 for stage IV. [Correction added on 05 October 2021 after first online publication: The estimation of health outcomes (QALYs) for all three interventions evaluated (synthetic mesh; biologic mesh; no mesh) have been corrected in this version.] Conclusions: Synthetic mesh was the most cost‐effective strategy to prevent the formation of PSH in patients after end colostomy for any rectal cancer stage; however, conclusions are dependent on which subset of RCTs are considered to provide the most robust evidence.